Growth of two‐layer copolymer as the stationary phase with very high separation efficiency for separating peptides in capillary electrochromatography. Issue 20 (29th August 2021) - Sun, Genlin; Tang, Weiyang; Lu, Yao; Row, Kyung Ho
Abstract: Open tubular CEC (OT‐CEC) column with a very high separation efficiency was prepared for peptides separation. A pretreated silica‐fused capillary was reacted with 3‐(methacryloxy) propyltrimethoxysilane followed by vinylbenzyl chloride and divinylbenzene to produce first thin monolithic monolayer. The second copolymer layer was formed on thin monolithic monolayer of the capillary by reversible addition‐fragmentation transfer polymerization of N ‐phenylacrylamide and styrene. The key parameters including buffer pH value and organic modifier were systematically evaluated to provide the optimal chromatographic condition. The resultant OT‐CEC columns were validated by separating a synthetic mixture of peptides and cytochrome C tryptic digest in capillary electrochromatography. The number of theoretical plates as high as 2.4 million per column was achieved for synthetic mixture peptides. In addition, the fabricated OT‐CEC column also resolved more than 18 high‐efficiency digestion peptides from a mixture containing tryptic digest of cytochrome C. The column to column and inter‐ to intraday repeatabilities of OT‐CEC column through RSD% were found better than 3.0%, exhibiting satisfactory stability and repeatability of the two‐layer deposited OT‐CEC column. The results reveal that the open tubular capillary column modified with two‐layer copolymer shows the great prospect for the separation of proteins in capillary electrochromatography.